Extrapulmonary manifestations of Mycoplasma pneumoniae infection in children - N. I. Kolganova; D. Yu Ovsyannikov; A. E. Angel; M. V. Biryukova; Sh. A. Gitinov; V/ V. Gorev; E. A. Degtyareva; E. V. Deeva; A. E. Kessel; O. I. Zhdanova; M. A. Karpenko; S. A. Nosov; et al. (LLC "Diagnostics and Vaccines", 2024)
Mycoplasma pneumoniae (M. pn.), which is a well-known pathogen to cause atypical pneumonia, in 25% of cases can lead to a wide range of extra-pulmonary symptoms, reflecting damage to almost any organ or organ system (skin and mucous membranes, nervous, cardiovascular, gastrointestinal, urinary system etc.). Aspecific syndrome Mycoplasma pneumoniae-induced rash and mucositis (MIRM) has been identified recently. Among the CNS manifestations associated with M. pn., acute postinfectious cerebellar ataxia is worth mentioning. In this article we present clinical cases of a 14-year-old boy and a 6-year-old girl with extrapulmonary manifestations of M. pn. infection. This article considers etiological, pathogenetic and clinical features of mycoplasma infection in children with an emphasis on extra-respiratory manifestations.